Primary squamous cell carcinoma of the thyroid: a rare type of thyroid cancer - Sisman, Pinar; Saraydaroglu, Ozlem; Sahin, Ahmet Bilgehan; Oz Gul, Ozen; Cander, Soner; Ersoy, Canan (The European Research Journal, 2017)
Primary squamous cell carcinoma of the thyroid is rare but aggressive malignancy. Primary treatment is complete surgical resection of the tumor. If surgical eradication of the tumor is not successful, it has poor prognosis although multimodality treatment. We report a case with multiple thyroid nodules of which fine needle aspiration cytology was suspicious for malignancy. After total thyroidectomy, well differentiated squamous cell carcinoma was observed in histopathological examination. Postoperative investigation ruled out metastasis of the other sites and recurrence has not been observed for 25 months. Early and accurate diagnosis is crucial to achieve complete cure with surgery and long-term survival.